Outcome and Associated Findings in Individuals with Pre- and Postnatal Diagnosis of Tetralogy of Fallot (TOF) and Prediction of Early Postnatal Intervention - Wolter, Aline; Gebert, Marie; Enzensberger, Christian; Kawecki, Andrea; Stessig, Rüdiger; Degenhardt, Jan; Ritgen, Jochen; Thul, Josef; Khalil, Markus; Herrmann, Johannes; Axt-Fliedner, Roland (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Purpose The aim of our retrospective evaluation was to compare the outcome of patients with prenatal and postnatal diagnosis of Tetralogy of Fallot (TOF) and to analyze prenatal echocardiographic parameters predicting intervention within 30 days postnatal.Materials and Methods We evaluated 142 patients in our pediatric heart center and prenatal diagnosis center and prenatal practice Praenatal plus in Cologne between 01/08–06/16.Results Within the prenatal diagnosis group, 6/74 fetuses (8.1 %) had TOF with pulmonary atresia (TOF-PA), and 6 (8.1 %) had absent pulmonary valve syndrome (TOF-APVS). 14 (18.9 %) had an abnormal karyotype including 9/14 (64.3 %) with microdeletion 22q11.2. 25 (33.8 %) had extracardiac malformation. 4 (5.4 %) had agenesis of ductus arteriosus (DA), 22 (29.7 %) had right aortic arch (RAA) and 9 (12.2 %) had major aortopulmonary collateral arteries (MAPCAs). Within the postnatal diagnosis group, no patient had TOF-PA, 4/68 (5.9 %) had TOF-APVS. 12 (17.6 %) had extracardiac malformations, 9 (13.2 %) had an abnormal karyotype including 2/9 with microdeletion 22q11.2. 10 (14.7 %) had RAA, 9 (13.2 %) had MAPCAs. There were no cases with agenesis of DA. Increasing z-score values of the left/right pulmonary artery (LPA/RPA) prenatally were associated with a lower probability for early postnatal intervention (RPA: p = 0.017; LPA: p = 0.013). Within the prenatal diagnosis group, 12 of 41 (29.3 %) live-born patients with follow-up and intention to treat needed early intervention versus 7 (10.3 %) in the postnatal diagnosis group (p = 0.02). Within the postnatal diagnosis group, there were no deaths, while 2 (4.9 %) post-intervention deaths occurred in the prenatal diagnosis group.Conclusion There are no significant differences concerning post-intervention survival in the prenatal diagnosis group versus the postnatal diagnosis group. Complex cases may be underrepresented in the postnatal diagnosis group. Smaller RPA/LPA values prenatally seem to be associated with early postnatal intervention.
Keywords: fetal echocardiography; congenital heart disease; Tetralogy of Fallot